Maternal Malignancy After Atypical Findings on Single-Nucleotide Polymorphism–Based Prenatal Cell-Free DNA Screening. Issue 4 (9th April 2023) - Goldring, Georgina; Trotter, Cindy; Meltzer, Jeffrey T.; Souter, Vivienne; Pais, Lynn; DiNonno, Wendy; Xu, Wenbo; Weitzel, Jeffrey N.; Vora, Neeta L.
Abstract : In a large cohort of patients, two thirds of individuals who had a noninvasive prenatal screening result concerning for maternal malignancy had a cancer diagnosis. Abstract : OBJECTIVE: To evaluate the incidence and clinical outcomes of cell-free DNA results suspicious for maternal malignancy on prenatal cell-free DNA screening with single-nucleotide polymorphism (SNP)–based technology. METHODS: This retrospective cohort study included data from SNP-based, noninvasive prenatal screening samples from a commercial laboratory from January 2015 to October 2021. Maternal plasma was screened for trisomy 21, 18, and 13; monosomy X; and triploidy. Cases were considered suspicious for maternal malignancy if retrospective bioinformatics and visual inspection of the SNP plot were suggestive of multiple maternal copy number variants across at least two of the tested chromosomes. Clinical follow-up on patients was obtained by contacting individual referring clinician offices by telephone, facsimile, or email. RESULTS: A total of 2, 004, 428 noninvasive prenatal screening samples during the study period met criteria for inclusion in the analysis. Of these, 38 samples (0.002% or 1 in 52, 748, 95% CI 1:74, 539–1:38, 430) had SNP-plot results that were suspicious for maternal malignancy. Maternal health outcomes were obtained in 30 of these patients (78.9%); eight were lost to follow-up. Maternal malignancy or suspected malignancy was identified in 66.7% (20/30) of the 30 patients with clinical follow-up provided by the clinic. The most common maternal malignancies were lymphoma (n=10), breast cancer (n=5), and colon cancer (n=3). CONCLUSION: Results suspicious for maternal malignancy are rare with SNP-based noninvasive prenatal screening (1:53, 000), but two thirds of patients who had a noninvasive prenatal screening result concerning for malignancy in this study had a cancer diagnosis. Investigation for malignancy should be recommended for all pregnant patients with this type of result. FUNDING SOURCE: This study was funded by Natera, Inc.